Politics and Psychoanalysis in the Times of the Generalized Metonymization - Šumič Riha, Jelica (Filozofski vestnik, 2012)
In this essay I propose to explore the status of the not all in politics and psychoanalysis by analyzing and bringing into question the seemingly self-evident relationship of the mutual exclusion between politics and psychoanalysis. I would argue that in order to expose an affinity in dealing with the ‘not all’ in politics and psychoanalysis, it is necessary to move beyond the traditionally hostile polarities of the singular and the universal and to reverse the usual perspective according to which there is no passage between the domain of the singular and the domain of the universal. I then move on to considering the relationship between psychoanalysis and politics from the point of view of the community ‘for all’ constituted through a complex practice of disidentification and the production of the ‘whatever’ singularities.